The Ethnic-Specific Spectrum of Germline Nucleotide Variants in DNA Damage Response and Repair Genes in Hereditary Breast and Ovarian Cancer Patients of Tatar Descent - Brovkina, Olga I.; Shigapova, Leila; Chudakova, Daria A.; Gordiev, Marat G.; Enikeev, Rafael F.; Druzhkov, Maxim O.; Khodyrev, Dmitriy S.; Shagimardanova, Elena I.; Nikitin, Alexey G.; Gusev, Oleg A. (Frontiers in Oncology, 2018)
Population of Russia consist of more than 100 ethnic groups and represent complexity and unique opportunity for identification of spectrum of rear hereditary pathogenic mutations. In order to get insights of landscape of heredity pathogenic variants we applied Targeted Next Generation Sequencing to analyse germline mutation load in DNA damage response and repair genes in Hereditary Breast and Ovary Cancer (HBOC) patients of Tatar ethnicity, representing approx. 7% of total population in Russia. Several pathogenic mutation markers were identified in DNA double strand breaks repair genes, and the spectrum of these markers in Tatar patients was found to be different to those that have been previously reported for patients of Slavic ancestry. The CDK12 gene encodes cyclin-dependent kinase 12 – the key transcriptional regulator of the genes involved in DNA damage response and repair. Analysis of CDK12 in a cohort of Tatar patients with HBOCS identified c.1047-2A>G nucleotide variant in CDK12 gene that was detected in 8/106 (7.6%) HBOCS patients of Tatar ethnicity, 1/93 (1.1%) HBOCS patients with mixed or unknown ethnicity, and in 1/238 (0.42%) healthy controls of mixed ethnicity (Tatars and non-Tatars) (p = 0.0066, OR = 11.18, CI 95% = 1.53–492.95, Tatar and non-Tatar patients vs healthy controls). In a group of mixed ethnicity patients from Tatarstan with sporadic breast and/or ovarian cancer this nucleotide variant was detected in 2/93 (2.2%) cases. In a cohort of participants of Slavic descent from Moscow comprising of 95 HBOCS patients, 80 patients with sporadic breast and/or ovarian cancer and 372 healthy controls this nucleotide variant was absent. Our study demonstrates strong predisposing role of CDK12 c.1047-2A>G nucleotide variant in HBOCS in patients of Tatar ethnicity and identifies CDK12 as a novel gene involved in susceptibility to HBOCS.